Determinan Niat Menggunakan Teknologi Blockchain pada Sistem Informasi Akuntansi dan Manajemen oleh Pegawai Pemerintah Daerah - Linda, Novia; Sofyani, Hafiez (E-Jurnal Akuntansi; Vol 34 No 3 (2024)DO - 10.24843/EJA.2024.v34.i03.p12, 2024)
This research aims to determine the willingness of local governments to use blockchain software in the Accounting and Management Information System (SIAM). Technology Organization Environment (TOE) theory is the theory adopted in this research. The sample for this research was employees of Regional Apparatus Organizations (OPD) in Sleman Regency by applying the purposive sampling method. This research is included in qualitative research which uses primary data in the form of direct questionnaires. To test the hypothesis, researchers used PLS with SmartPLS v.04 software. Computer anxiety has a negative effect on intention to use blockchain. This means that the higher the computer anxiety, the lower the intention to adopt blockchain. Meanwhile, data privacy security, top management support, and competitive pressure have a positive influence on intention to use blockchain. Data privacy security, top management support, and competitive pressure directly influence the intention to use blockchain technology. Keywords: Blockchain; MAIS ; Regional Government ; TOE